(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotatsiya . Mazkur maqolada inflatsiyaning kelib chiqish sabablari va uning iqtisodiyotga ta‘siri tahlil qilinadi. Inflatsiya asosan talab va taklif o‘rtasidagi nomutanosiblik, ishlab chiqarish xarajatlarining oshishi, pul massasi ortishi kabi omillar natijasida yuzaga kelishi tushuntirilgan. Shuningdek, inflatsiyaning turli shakllari, jumladan, talab inflatsiyasi va taklif inflatsiyasi turlari haqida ma‘lumot berilgan. Maqolada inflatsiyani oldini olish va uni boshqarish usullari ham ko‘rib chiqilgan. Ushbu maqola iqtisodiy barqarorlikni ta‘minlash va inflatsiya jarayonlarini chuqur tushunish istagida bo‘lgan mutaxassislar, tadqiqotchilar va talabalar uchun foydalidir. Annotation. This article analyzes the causes of inflation and its impact on the economy. Inflation arises mainly due to imbalances between supply and demand, increased production costs, and the growth of the money supply. Various types of inflation, including demand- pull inflation and cost- push inflation, are also discussed. The article examines methods to prevent and control inflation. It will be useful for specialists, researchers, and students interested ensuring economic stability and gaining I deeper understanding of inflationary processes. Annotation. This article analyzes the causes of inflation and its impact on the economy. Inflation arises mainly due to imbalances between supply and demand, increased production costs, and the growth of the money supply. Various types of inflation, including demand- pull inflation and cost- push inflation, are also discussed. The article examines methods to prevent and control inflation. It will be useful for specialists, researchers, and students interested ensuring economic stability and gaining I deeper understanding of inflationary processes. Аннотация. В данной статье анализируются причины возникновения инфляции и ее влияние на экономику. Инфляция обьясняется как результат дисбаланса между спросом и предложением увеличения затрат на производство роста денежной массы и других факторов. Также приведена информация о различных формах инфляции, в том числе инфляции спроса и инфляции предложения. В статье рассмотрены методы предотвращения и регулирования инфляции. Данный материал будет полезен специалистам, исследователям и студентам, стремящимся глубже понять процессы инфляции и пути обеспечения экономической стабильности.